Profitability of selected microfinance institutions: Determining financial performance amidst covid-19 pandemic - Daquis, Justine Kyle Lynnette M., Estoque, Frierze Gyroe G., Labarda, Elysia Ashlyn R., Lontabo, Jeferson A., Lopez, Morella, Morales, Leslie A. 4 0 16; 5 (2023)
Abstract Microfinance Institutions (MFIs) are known to provide financial services to the unbanked with a goal in mind to somehow improve their living standards. MFIs are bound to reach the low- income household or specifically the rural poor for them to attain financial inclusion. MFIs provides microcredit to the underserved with the purpose of helping those in need to gain sales and earn profit as they expand their business (Awajobi, 2019). The purpose of this study is to know the Profitability of Selected Microfinance Institutions: Determining Financial Performance Amidst COVID-19 Pandemic. This study focuses on two selected Microfinance Institutions which are the ASA Philippines Foundation located in Pasig and BPI Direct BanKo located in San Juan. The researchers used secondary data in collecting needed information to achieve the objective of the study. For the secondary data, the researchers collected the financial statement of both ASA Philippines Foundation and BPI Direct Banko for the year 2017-2021. The financial performance of ASA Philippines Foundation, Inc., and BPI Direct Banko, Inc., had a significant drawback for year 2020 as the peak of the pandemic arise. The researchers were able to compute this through the net profit margin, gross profit margin, common sizing, and trend line analysis. The researchers also had a comprehensive analyzation of the financial statements to be able to determine and explain accordingly the significant changes from the year 2019 to 2021. The gap in the study is that the selected MFIs do not have an existing policy with regards to the allowance for impairment on unforeseeable economic events especially pandemic where the members of the said institutions are from low-income households that limits the clients' capacity to pay.
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2